APPLICATION OF TEST CONTROL AS OBJECTIVE METHODICAL TECNIQUE FOR EVALUATION OF QUALITY OF EDUCATION - Карпець, М.В. (World of Medicine and Biology, 2014)
The article examines the benefits of test control as a means of educational assessment, the experience of teaching "Medical Chemistry" for first-year students at a credit-module system.